Pichadores de rua, territorialidades urbanas em conflito: territórios (in)visíveis de Goiânia - Masson, José Renato (2004)
The street pitchers, look for the introduction, especially in big and medium sized cities, of their pieces of graffiti, willing to demarcate territories, attack the urban scene and provoke the rival groups. The pitch can not be understood as an act of vandalism:they mean to be present on the city’s routine, “re”presenting and signifying again the scenery. The Movement cropped up in Bronx’s urban ghettos, USA, spreaded out around the world, and in Goiânia, there are many “groups”, that can be categorized in 2 types.In the first one,members of groups of rooters,compete with each other aroundthe metropolis signing the acronyms TEV (Torcida Esquadra Vilanovense) and FJG (Força Jovem do Goias). And the neighbourhood groups, like the MGC (Moleques Grafiteiros do Crimeia), BF (Bairro Feliz), UPS (União dos Pichadores Skatistas), etc. This groups search for the demarcation and the consolidation of the terrritory facing off the opponent, exerting territoriality, over an especific area. At the same time, they constitute a self identity, withthe intention to put down and to oppose to the conventional urban patterns.Geography must not abstein it self from the comprehension of this phenomenon, once this understanding straightly involves the categories of geographical analysis, such as territory, teritoriality and identity.